Can accounting value relevance and pricing error influence stock price of high-technology service enterprises? - Citra Sukmadilaga; Jose Christian Santoso; Erlane K. Ghani (Economies, 2023)
This study examines whether relevant accounting ratios influence the stock prices of high-technology service enterprises in five countries, namely, the United States, Japan, China, the United Kingdom, and France. Subsequently, this study determines the existence of pricing error (if any) between the intrinsic value and the market value of the stock price due to the accounting ratios. Content analysis was performed on the annual reports of 326 high-technology service enterprises to determine the effect of three accounting ratios, namely diluted earnings per share, revenue per share, and book value per share, on the stock price of the high-technology service enterprises. This study shows that diluted earnings per share and book value per share influence the stock price of high-technology service enterprises. However, this study shows revenue per share does not influence the stock price of high-technology service enterprises. In addition, this study shows that, on average, the pricing error of high-technology services enterprises is considered moderate, with some countries exhibiting higher pricing errors. This study provides insight into how much accounting ratios can influence the movement of stock prices and, in turn, assist investors in understanding the key metrics within the high-technology industry.
Keywords: 330; book value per share; earnings per share; high-technology service enterprises; intrinsic value; pricing error; revenue per share; stock price